Designing electronic graphic symbol-based AAC systems: a scoping review. Part 2: application of human-centred design. - Tönsing, Kerstin; Bartram, Jessica; Morwane, Refilwe E.; Waller, Annalu (Disability & Rehabilitation: Assistive Technology, 2024)
This is the second of two papers summarizing studies reporting on the design of electronic graphic symbol-based augmentative and alternative communication (AAC) systems. The aim of this paper was to describe the design approaches used and to determine to what extent the principles of human-centred design (HCD) were reflected in the design approaches and processes used. A scoping review was conducted. A multifaceted search resulted in the identification of 28 studies meeting the selection criteria. Data were extracted relating to four areas of interest, namely, (1) the general characteristics of the studies, (2) features of the systems designed, (3) availability of the systems to the public and (4) the design processes followed. In this paper, findings related to the last area are presented. Design approaches were often inconsistently described. User-centred design was mentioned more often than HCD. Even so, various HCD principles were considered in most studies. Notably, stakeholders were involved in the design process in all studies. However, users were not involved in all studies and stakeholder roles were predominantly informative rather than collaborative. Prototype and product evaluations focussed mostly on usability rather than user experience. Although many design teams were multidisciplinary, engineers and computer scientists predominated. There is a need for designers to be more transparent about the type of design approach used to guide the system design and also to clearly report on design approaches and processes used. The application of HCD to the design of graphic symbol-based AAC systems is still limited. Human-centred design approaches can productively guide the design of electronic graphic symbol-based augmentative and alternative communication (AAC) systems. Creative methods are needed to involve stakeholders with complex communication needs in all phases of the design process. Evaluation of electronic graphic symbol-based AAC systems should consider both usability and user experience.